Stability of genetic divergence among eggplant accesses in three stages of development - Silva, Derly José Henriques da; Costa, Cyro Paulino da; Cruz, Cosme Damião; Casali, Vicente Wagner Dias; Dias, Luíz Antonio dos Santos (Crop Breeding and Applied Biotechnology, 2001)
Genetic divergence stability among 19 eggplant accesses was estimated in three stages of development: vegetative, reproductive and productive. The experiment was carried out in a randomized block design, with three replications and four plants per plot. For each developmental stage, the divergence was calculated from 12, 12 and 5 characteristics, respectively. The cluster analysis, applied to the genetic distance matrix (D2 ), showed the formation of two clusters in the vegetative stage, four in the reproductive stage and six in the productive stage. Therefore, it was obseved that productive stage characteristics have greater discriminatory capacity. However, inconsistency in respect to the number and composition of clusters formed in different stages was observed. It can be concluded that the genetic divergence estimated among accesses is related only to the variability of the characteristics used in its estimation, and that extrapolation of this variability to other characters may lead to wrong interpretations.
Keywords: Solanum melongena; Genetic resources; Breeding; Multivariate analysis